Captain Underpants and the wrath of the wicked Wedgie Woman - Pilkey, Dav, 1966-; Garibaldi, Jose. (New York, NY : Scholastic, Inc., 2001)
When Harold and George turn fourth-grade teacher Ms. Ribble into the evil Wedgie Woman, she gives the wedgie of doom to unsuspecting people who stand in her way--including principal-turned-superhero Captain Underpants.
"Now in full color."
Electronic audio file.
Read by Len Forgione.
Keywords: Imagination -- Juvenile fiction; Schools -- Juvenile fiction; School principals -- Juvenile fiction; Heroes -- Juvenile fiction; Imagination -- Fiction; Schools -- Fiction; School principals -- Fiction; Heroes -- Fiction; Humorous stories; Humorous fiction; Downloadable audiobooks; Audiobooks